Detection of Bk Polyomavirus Antigen in Patients with Acute Lymphoblastic Leukemia - H Ali , Safa; Satti , Sawsan; H Ali , Alaa; B Al-Obaidi, Asmaa (Diyala Journal of Medicine, 2023)
Background: BK polyomavirus that is acquired in early childhood as BKPyV is near ubiquitous in adults with a seroprevalence of >80%, it has been found as the main cause of hemorrhagic cystitis in hematopoietic stem cell transplantation patients, due to immunosuppression regimen that lead to the activation of the virus from the latency status and lead to increased viral shedding in urine (viuria). Objective: To investigate the frequency of BK Polyomavirus antigen excretion in urine of children with acute lymphoblastic leukemia with and without chemotherapy and compare it with normal controls. Patients and Methods: A case-control study conducted from December 2021 to May 2022 in Baghdad, Iraq on leukemia patients of Central Pediatrics Hospital (Al-Eskan ). Urine samples and urine sediment smears were collected from 60 acute lymphoblastic leukemia patients. And compared with 60 apparently healthy age and sex-matched children, BK polyomavirus antigen in urine was detected using Enzyme-linked Immunosorbent Assay and urine cytology were Pap stained for the detection of decoy cells (DCs). Results: Positive BKPyV antigen in urine was seen in 55 (91.7%) of Acute lymphoblastic leukemia patients and 39 (65.0%) in controls (p=<0.001) and all the patients were decoy negative. There was no significant effect of the positivity of antigenuria on neither leukocytes level nor on the occurance of relapse in leukemia patients. Conclusion: The very high frequency of BKPyV in the urine signifies the importance of reactivation of this virus in ALL patients with and without chemotherapy.